Development of Novel Formulations to Enhance in Vivo Transdermal Permeation of Tocopherol - Nada Aly H.; Zaghloul Abdelazim A.; Hedaya Mohsen M.; Khattab Ibrahim S. (Acta Pharmaceutica)
Tocopherol represents a big challenge for transdermal permeation owing to its extreme hydrophobicity and large molecular mass. The aim of the present study was to develop alpha-tocopherol (T) topical formulations and evaluate their ex vivo and in vivo permeation. Franz diffusion cells were used for ex vivo permeation, and neonatal rats were used for in vivo permeation. Seven gel formulations and 21 liquid formulations were investigated for physical stability, viscosity and permeation of T. Analysis of T was performed by a validated HPLC method using a UV detector. The ex vivo permeation from gel and emulsion formulations was very poor (0.001-0.015 %). Highest permeation was observed from monophasic liquid formulations containing dimethyl sulfoxide (DMSO), tocopheryl polyethylene glycols (TPGs), propylene glycol, ethanol and 9.5 % T. The in vivo results demonstrated higher retention in the epidermis compared to subcutaneous tissues, 1377 and 1.13 μg g-1, respectively. Increasing T concentration from 4.8 to 9.5 % did not increase the amount permeated or % of T retained. It was concluded that simple solutions of T in the presence of DMSO and TPGs were more promising systems for effective transdermal permeation compared to gel, emulsion or oleaginous systems.